Analisis Pengaruh Penerapan Good Corporate Governance Terhadap Pengungkapan Sustainability Reporting: (Studi Konseptual) - Amelia Putri Hapsari (AKUNTANSI 45, 2023)
Corporate governance shows how an organization is managed and controlled to achieve corporate goals and provide stakeholder rights. Sustainability report disclosure is certainly influenced by corporate governance in a company. The purpose of this study is to analyze the effect of Good Corporate Governance (GCG) on the disclosure of sustainability reports. This research is a conceptual research that focuses on studying theoretical studies on a problem. The type of research used is descriptive research using a qualitative approach. This study uses data analysis methods with the data used in the form of secondary data, namely in the form of previous research articles as a literature study in accordance with the topic of discussion in this study. The discussion used in this research is whether the size of the board of commissioners, audit committee, and the size of a company can affect the disclosure of this sustainability report. The results of the study show that these three things do not affect the results of the sustainability reporting issued by the company.